Planning and Developing a Family-Based Psychological Intervention: Evaluating Impact on the Marital Satisfaction in Employed Parents with Adolescent Children - Narges Zainali; Gholam ali Afrooz; Masoud Lavasani; Sogand Ghasemzadeh (پژوهش‌های کاربردی روانشناختی, 2020)
The purpose of this study was to evaluate the impact of the family-based psychological intervention program on the marital satisfaction of employed parents with adolescent children. The research method build on quasi-experimental, (experimental and control groups with with pre-test and post-test). A total of 30 employed parents working in a governmental organization, with having at least one child between 11-16 years, were selected and randomly assigned into two equal experimental and control groups. The experimental group was trained with the psychological intervention program, consisting of 12 sessions of group training (90 minutes once a week).The control group did not receive any interventions during this period. The research tools were Demographic characteristics questionnaire, Needs Assessment and Afrooz Marital Satisfaction Scale (2010) (AMSS). Data analysis was done by repeated ـ measures MANCOVA. The results of the study showed that there was a significant difference between the experimental and control groups in the level of satisfaction of paired (P <0.05) and the intervention program The compilation improved the parity satisfaction of all sub-scales, and these results were sustained in three-month follow-ups.